Analysis of intercity bus public transport safety perception modeling using conjoint - Suraji, Aji; Djakfar, Ludfi; Wicaksono, Achmad; Marjono, Marjono; Putranto, Leksmono Suryo; Susilo, Sugeng Hadi (Eastern-European Journal of Enterprise Technologies, 2021)
Public transport safety is still an issue that needs to be studied by bureaucrats and researchers. This is because public bus accidents are still quite high. This is because many families, involved in traffic accidents, are shocked by the accident. Therefore, the problem of perception of a safe bus needs to be studied. The purpose of this study was to determine the perception model of a safe public bus. Mathematical modeling based on the parameters that have been studied was selected first. While the second objective was to determine the importance value of the parameters that are an indication of the perception of the safety of intercity bus public transportation. This research is a type of perceptual one where the data is taken from the relevant respondents. The method of data collection was carried out using a questionnaire with respondents from bus company owners, drivers, and passengers in the province of East Java, Indonesia. Respondents were asked to answer questions related to the variables of income, speed, comfort, and safety. The method of conjoint analysis is used. The first stage is the result of modeling the perception of a safe bus. Further analysis is carried out to obtain the importance value of the parameters. The result of this research is a utility model for the perception of a safe bus, which is expressed by the equation U, where the variables include income, speed, comfort, and safety. The highest level of importance is income 33.29 %, followed by the security variable with a weight of 25.39 %. This shows that the income factor is a top priority for drivers and management of bus company owners, while road safety is second only to income. In other words, respondents’ perceptions are more concerned with income, while safety is still a non-priority factor.